The relation of neck circumference and coronary artery disease risk factors and obesity indexes - Asgari, Ali; Niksirat, Kasra; Soleimani, Saeed (Advances in Nursing & Midwifery, 2017)
Abstract Background and Objectives: Coronary artery disease is the most common cause of death throughout the world. There is a relation between central obesity and glucose intolerance, hyperinsulinemia, diabetes, gout, and hyper-triglyceridemia rather than lower body obesity. Neck circumference is one of the new indices of obesity because of easily measurement. The aim of this study was to determine the relationship between neck circumference and other indices of obesity included waist circumference, body mass index, waist to hip circumference, waist-to-height ratio, body-fat percent and cardiovascular risk factors in a group of healthy individuals. Materials and Methods: This was a cross-sectional study in which 131 healthy subjects, including 50 men and 81 women were evaluated for relation between neck circumference and risk factors of cardiovascular diseases. Data were analyzed by SPSS-16 using ROC, Chi-square, and Pearson correlation coefficient tests. Results: Mean upper standard neck circumferences were 39 cm and 36 cm in men and women, respectively. In women with elevated neck circumference, weight, waist circumference, height, LDL, systolic blood pressure and body mass index were significantly higher than those with lesser than standard neck circumference. Furthermore, weight, waist circumference, hip circumference, systolic and diastolic blood pressure in men with high neck circumference was considerably higher than those that lesser than usual neck circumference (P <0.05). Conclusion: The high neck circumference was associated with some cardiovascular risk factors. These variables are the same variables indicative of obesity. Excess fat around the neck is associated with weight gain. This index can be a simple criterion for assessing of people exposed to obesity and is a means for screening. Key words: neck circumference, cardiovascular diseases, risk factors